Islamic Business Ethics in Creative Industry: Honesty and Business Sustainability in Digital Era - Nanang Setiawan; Achmad Hasan Basri; Azwar Cholili; Muhammad Mujib; Joko Hadi Purnomo (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Digitalization and increasing market competition require business actors to adapt rapidly, often giving rise to ethical dilemmas. This study aims to analyze the implementation of Islamic business ethics in the creative industry in the digital era, with a particular emphasis on honesty (ṣidq) as a fundamental principle supporting business sustainability. This qualitative study employs a literature review and in-depth interviews with three creative industry practitioners in Lamongan Regency, East Java, consisting of owners of a food and beverage (F&B) business, a mobile phone retail business, and a photography service (photo studio) business. Based on the empirical narratives of these three business owners, the findings reveal that honesty is operationalized in concrete business practices, including transparent pricing, truthful product descriptions, consistency between digital promotion and actual product quality, and openness in communicating service limitations. Despite challenges such as intense price competition, pressure for rapid production, and aggressive digital marketing practices, the informants consciously avoid misleading promotions and exaggerated claims. In the Lamongan context, honesty functions not only as a moral–religious value but also as a practical mechanism for building consumer trust and maintaining business reputation, which in turn supports long-term business sustainability. This study contributes to the literature by offering micro-level empirical insights into how honesty is enacted as a strategic ethical practice in small-scale digital creative businesses, rather than treating Islamic business ethics merely as a normative framework. Practically, the findings offer insights for practitioners and policymakers on integrating ethical and religious values into digital business strategies to enhance trust and sustainability.